A Cambodian prison portrait : one year in the Khmer Rouge's S-21 - Vann Nath, 1946- (Bangkok : White Lotus, 1998)
Account of an artist's experiences in prison during the Khmer Rouge regime in Cambodia.
Keywords: Vann Nath, -- 1946-; Political atrocities -- Cambodia; Political prisoners -- Cambodia -- Biography; Cambodia -- Politics and government -- 1975-1979.